2016
DOI: 10.4236/gep.2016.45003
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Assessment of Marine Debris, Seawater Quality and Littering in Ghana

Abstract: A baseline survey was carried out at four beaches along Ghana's Accra-Tema coastline over a period of sixteen weeks to determine beach quality, seawater quality and the perception of beach users towards littering. A total of 18,241 items of marine debris which weighed 297.59 kg were collected. Plastic materials were the dominant debris, accounting for 63.72% of total debris. Landbased marine debris formed the largest proportion of debris collected (93% of items/m 2 and 85 kg/m 2 ). Water quality analysis revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
2
13
1
Order By: Relevance
“…The statistical analysis backs up the observation and demonstrates how La Pleasure Beach has been managed. This contrasts favorably with the survey conducted by Van Dyck et al (2016); Sakumono Beach had more trash than La Pleasure Beach.…”
Section: The Spatial and Temporal Abundance Of Marine Littercontrasting
confidence: 81%
See 2 more Smart Citations
“…The statistical analysis backs up the observation and demonstrates how La Pleasure Beach has been managed. This contrasts favorably with the survey conducted by Van Dyck et al (2016); Sakumono Beach had more trash than La Pleasure Beach.…”
Section: The Spatial and Temporal Abundance Of Marine Littercontrasting
confidence: 81%
“…This result is comparable to other surveys conducted on beaches in South Africa (STAP 2011b) and a few other carefully chosen European beaches (OSPAR 2007). The percentages of plastics found at the Sakumono and La Pleasure Beaches (66% by weight and 73% by number) also favorably contrast with those found by Van Dyck et al (2016). This supports the claim that, globally, plastics account for 60 to 80% of all marine litter collected (Derraik 2002;(2011a).…”
Section: Types and Quantities Of Marine Littersupporting
confidence: 74%
See 1 more Smart Citation
“…The west African country Ghana boasts a coastline stretching about 550km, facing the Gulf of Guinea. Accra, the coastal capital, is home to around 3 million people and faces substantial waste management challenges, especially with regards to plastic litter 31 .…”
Section: Resultsmentioning
confidence: 99%
“…(2016) examined the effects of a smoking ban in Mexico and found that the ban was generally ineffective in reducing cigarette butt littering. A study in Ghana suggests that an already littered environment and the lack of authorities’ interest are the main reasons for increased littering (Van Dyck et al., 2016). Al‐Mosa et al.…”
Section: Discussionmentioning
confidence: 99%